PERAN GURU PPKn DALAM UPAYA MENCEGAH KENAKALAN SISWA SMP NEGERI 3 SAMPANG - Amir Hamzah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Keguruan dan Ilmu Pendidikan PGRI Sampang, Indonesia, 2024)
Education is urgently needed to help students develop themselves in the moral and psychological dimensions. In fact, there are still often students who fall into acts that are beyond the limits of reasonableness and violate applicable values and norms or better known as juvenile delinquency. Likewise, when learning is still taking place often in the classroom, students who have crossed the limit of reasonableness. Even one of the subjects, namely Pancasila and Citizenship Education (PPKn) which specifically teaches material on character education, moral development, manners and discipline, is also not spared from the deviant behaviors of students who sometimes disturb others, especially teachers who play a role in guiding students in a better direction. This type of research is qualitative descriptive with data collection techniques through observation, interviews and documentation. The results of this study show that: 1) the factors that cause the problem of juvenile delinquency at school are: lack of attention from parents and the influence of the surrounding environment. 2) the obstacles experienced by PPKn teachers in overcoming the problem of juvenile delinquency in schools are: lack of student awareness, association with naughty friends, and lack of supervision and synergy with teachers at school and parents. 3) the role of PPKn teachers in tackling the problem of juvenile delinquency in schools, namely: as a guide, as a model or example, finding out student problems, and taking a special approach.